Effects of Well-being, Grit, Emotion Regulation, and Resilience Interventions on L2 Learners' Writing Skills - Shafiee Rad, Hanieh; Jafarpour, Aliakbar (Reading & writing quarterly, 2023)
Positive emotions (pleasant or desirable situational responses) are proliferated in recent years and their effect on academic achievement has been documented in the literature, while their effect in the specific domain of second language learning (L2) remains underexplored. Since successful mastery of an L2 is highly dependent on learners' positive emotions, therefore, enhancing these emotions can result in a higher level of proficiency. The current study was an effort to examine the role of well-being, grit, emotion regulation, and resilience interventions on both L2 learners' writing achievement and enhancement of their positive emotions well-being, grit, emotion regulation, and resilience in analysis. To this end, two intact classrooms (N Experimental = 36 and N Control = 34; age M = 21.67, SD = 1.23) were selected in an English language institute and received 10 sessions of writing instruction (both groups) and intervention (only experimental group). Data were gathered through writing tasks and questionnaires. Results suggest that positive emotions interventions have a positive and significant effect on L2 learners' well-being, grit, emotion regulation, and resilience in a writing classroom. Furthermore, we found that well-being, grit, emotion regulation, and resilience intervention can significantly improve L2 learners' writing skills. In sum, it can be suggested that employing positive emotions intervention not only can improve individuals' emotions but also can improve their learning skills. This study proposed that developing positive psychology may offer opportunities to improve affective, personal, and educational gains.